The role of liquid biopsy in the diagnosis of glioblastoma progression - A. I. Ryabova; V. A. Novikov; E. L. Choynzonov; L. V. Spirina; N. V. Yunusova; A. A. Ponomareva; S. N. Tamkovich; O. V. Gribova (Сибирский онкологический журнал, 2022)
Purpose: to summarize available data on the diagnostic value of various circulating biomarkers for the detection of glioblastoma recurrence.Material and Methods. A literature search was conducted using PubMED ExoCarta and SILVA databases.Results. Glioblastoma multiforme (GBM) is the most common glioma in adults with an unfavorable prognosis. Treatment of tumor recurrence can improve the survival of patients. Neuroimaging is the standard method of diagnosing brain tumor recurrence. However, a neuroimaging method to clearly distinguish between pseudo progression and tumor progression has not been found to date. Current molecular tumor profling relies heavily on tissue resection or biopsy. Tissue profling has several disadvantages in the central nervous system’s tumors, including the challenge associated with invasive biopsy, the heterogeneous nature of many malignancies where a small biopsy can under represent the mutational profle. Liquid biopsy is a promising method in diagnosing malignant tumors. Blood collection is a simple, minimally invasive procedure, but cerebrospinal fuid allows tumor markers to be detected more confdently. However, collection of cerebrospinal fuid is a complex and invasive procedure that can be accompanied by serious complications.Conclusion. Biological fuid markers such as circulating tumor cells, extracellular vesicles, cell-free DNA and cell-free RNA allow for the detection of GMB, determination of molecular genetic features of cancer during response to therapy, and early detection of GBM recurrence.